2003
DOI: 10.1038/sj.bjc.6601260
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 and CAIX as intrinsic markers of hypoxia in bladder cancer: relationship with vascularity and proliferation as predictors of outcome of ARCON

Abstract: Glucose transporter-1 protein (GLUT1) and carbonic anhydrase IX (CAIX) are regulated by hypoxia inducible factor-1 (HIF-1) and have been studied as putative intrinsic cellular markers for hypoxia. This study directly compares CAIX and GLUT1 with pimonidazole binding in a prospective series of bladder cancer patients and also studies the prognostic significance of the markers, in combination with vascularity and proliferation, in a retrospective series of bladder cancer patients treated in a phase II trial of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
134
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 28 publications
10
134
3
2
Order By: Relevance
“…Carbonic anhydrase IX is induced by hypoxia in a range of tumour cell lines in an HIF-1-dependent manner (Wykoff et al, Cancer Research, 2000), its role being to regulate tissue pH (Svastova et al, FEBS Letters, 2004). Studies have directly and indirectly validated the use of CA IX as an intrinsic surrogate marker of hypoxia (Loncaster et al 2001;Turner et al, 2002;Hoskin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonic anhydrase IX is induced by hypoxia in a range of tumour cell lines in an HIF-1-dependent manner (Wykoff et al, Cancer Research, 2000), its role being to regulate tissue pH (Svastova et al, FEBS Letters, 2004). Studies have directly and indirectly validated the use of CA IX as an intrinsic surrogate marker of hypoxia (Loncaster et al 2001;Turner et al, 2002;Hoskin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Carbonic anhydrase IX is induced by hypoxia in a range of tumour cell lines in an hypoxia-inducible factor-1 (HIF-1)-dependent manner (Wykoff et al, Cancer Research, 2000), its role being to regulate tissue pH (Svastova et al, FEBS Lett, 2004). Studies have directly and indirectly validated the use of CA IX, as an intrinsic surrogate marker of hypoxia (Loncaster et al, 2001;Turner et al, 2002;Hoskin et al, 2003). In order to understand the contribution of hypoxia to tumour progression, resistance to treatment, and, in the future, to exploit differential expression of hypoxia-related factors in tumours vs normal tissue for therapeutic gain, we have examined the expression of CA IX in breast cancer and related this to clinico-pathological parameters and clinical outcome.…”
mentioning
confidence: 99%
“…Hoskin et al (2003) showed that GLUT1 and CAIX expressions in invasive bladder cancer were correlated with hypoxia and outcome of radiation therapy. However, there is also an individual pattern of expression for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…One aim of the present study was to establish the efficacy of AQ4N in a cisplatin-based chemoradiation schedule in human xenografts using clinically relevant fractionation protocols. Lung and bladder xenografts were seen as relevant models for these evaluations as radiotherapy with platinum chemotherapy is commonly applied in the clinical setting, and hypoxia has been identified as a potential cause of therapy failure in both diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical importance of hypoxia is increasingly widely recognized, there remains some controversy in the choice of method for quantifying hypoxia (26). Glut1 is well recognized to be regulated by hypoxia, and there are numerous studies demonstrating its utility as a marker of endogenous hypoxia and its association with tumor aggressiveness and poor prognosis in numerous diseases (24)(25)(26)(27). The use of an endogenous marker of hypoxia such as Glut1 does not require exogenous administration of an agent such as pimonidazole and, thus, facilitates the translation of any preclinical findings into a clinical context.…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 99%